PERANCANGAN RUMAH TAHANAN POLDA GORONTALO DENGAN PENDEKATAN ARSITEKTUR HUMANIS - Labaika, Fikransyah; Arifin, Sri Sutarni; Mokodongan, Elvie Fatmah (JAMBURA Journal of Architecture, 2024)
The majority of inmates in Indonesia’s prison and correctional intitutions is increasing annually due to an overpopulation of in mates. The situation is the cause of prison breakout, riots, drug trafficking, and various other possibilities. The increase in the resident population in the correctional facility has not been matched by the fulfillment of proper housing capacity for inmates and detainees. In Gorontalo Province, in the Gorontalo Regional Police, crimes such as violence, beatings, murders, domestic violence, and so on are caused by someone consuming alcohol. Distruption of public safety and order (Kamtibmas) in Gorontalo Province from January to March 2021, there were 628 police reports that were handled by the Directorate of General Criminal Investigation of the Gorontalo Police and the Criminal Reserve Unit (Satreskrim) Police Resort ranks. The cases were comprised of 226 casas of abuse, 174 cases of fraud/embezzlement, 135 cases of theft, 36 cases of child protection, 30 cases of domestic violence, and 27 cases of defamation/insult. The methodology used was data collection, both secondary and primary data, which can support the process of design reference for the Gorontalo Police Detention House with a humanist architectural approach, followed by analytical methods in the form of site analysis and building analysis. The result of this study is a design of the Gorontalo Police Detention Center with a humanist architectural approach to take into account the emotional and social requirements of inmates. It is intended that this will contribute to a more effective rehabilitation process. By fostering a more pleasant environment and supporting the rehabilitation process, it is anticipated that the crime rate in the community will decrease.  Sebagian besar penghuni rumah tahanan dan lembaga pemasyarakatan di Indonesia setiap tahunnnya semakin meningkat dengan kelebihan penghuni. Situasi ini merupakan penyebab dari kaburnya narapidana, kerusuhan, peredaran narkotika, dan berbagai kemungkinan lainnya. Peningkatan populasi penghuni dalam rumah tahanan tidak diimbangi dengan pemenuhan kapasitas hunian narapidana dan tahanan yang layak. Di Provinsi Gorontalo dalam instasi Polda Gorontalo, kriminalitas yang terjadi seperti kekerasan, pengoroyokan, pembunuhan, KDRT dan lain sebagainya ini merupakan salah satu disebabkan oleh Miras yang di konsumsi oleh seseorang. Gangguan Kamtibmas di Provinsi Gorontalo dari bulan Januari-Maret 2021, terdapat 628 laporan polisi yang telah ditangani oleh Direktorat Reskrim Umum Polda Gorontalo dan Satreskrim Polres jajaran. Dari 628 kasus ini terdapat, penganiayaan 226 kasus, penipuan/penggelapan 174 kasus, pencurian 135 kasus, perlindungan anak 36 kasus, KDRT 30 kasus dan Pencemaran nama baik/penghinaan 27 kasus. Metodologi yang di terapkan dalam penyususan adalah pengumpulan data baik data sekunder maupun data primer yang dapat menunjang proses penyusunan acuan Perancangan Rumah Tahanan Polda Gorontalo dengan pendekatan arsitektur humanis, kemudian dilanjutkan dengan metode analisa berupa analisa tapak dan analisa bangunan. Berdasarkan analisa yang dilakukan maka hasil yang diperoleh perancangan Rumah Tahanan Polda Gorontalo dengan pendekatan arsitektur humanis bertujuan untuk memperhatikan kebutuhan emosional dan sosial para tahanan diharapkan dapat membantu dalam proses rehabilitasi yang lebih efektif. Mengurangi tingkat kejahatan di masyarakat, dengan menciptakan lingkungan yang lebih nyaman dan membantu dalam proses rehabilitasi, diharapkan dapat mengurangi tingkat kejahatan di masyarakat.